Comparison of Application of Project Management Theories in Software Development Project to Startup Company Based On Project: Case Study of PT Skatsa Data Integra (Journal of Business and Management, 2021)
The development of business environment in Indonesia is very rapid, especially in telecommunication field. The sector of information and communication achieved the highest positive growth rate in Q2-2020 which contributed 4.66 percent of the GDP structure. One of the IT companies in Indonesia is PT Skatsa Data Integra, which runs their business based on IT project. This start-up has a problem with inefficiency for completing a project. In some situations, they cannot take other projects because they worry about the insufficient time. Due to this problem, the company is not able to reach the expected target. PT. Skatsa Data Integra is chosen as a case study because this kind of problem can contribute to the development of IT business in Indonesia. The purpose of the research is to identify the root problem in project management system in PT. Skatsa Data Integra and find the solution using CRT with five key elements of CRT. This research uses three methods to solve the problem: CPM, SCRUM, and KANBAN methods. The result shows that the project manager cannot breakdown the project properly. The manager uses judgemental decision to complete the project instead. This research solves the problem by implementing the three methods to the project. It makes improvement at time efficiency. At CPM there are 50% improvement by decreasing project time. At Kanban, there are 55% improvement by decreasing time. And in last method SCRUM, there are no improvement in time, but the improvement is minimize error from each activity. The other improvement are resources. Every method has improvement to add more resources to maximize the efficiency of project. Keywords: Project Management Method, Software Development Project, Start-up Business, Telecommunication, Efficiency